Single-molecule imaging and quantification of the immune-variant adhesin VAR2CSA on knobs of Plasmodium falciparum-infected erythrocytes - Sanchez, Cecilia P. (Commun Biol, 2019)
PfEMP1 (erythrocyte membrane protein 1) adhesins play a pivotal role in the pathophysiology of falciparum malaria, by mediating sequestration of Plasmodium falciparum-infected erythrocytes in the microvasculature. PfEMP1 variants are expressed by var genes and are presented on membrane elevations, termed knobs. However, the organization of PfEMP1 on knobs is largely unclear. Here, we use super-resolution microscopy and genetically altered parasites expressing a modified var2csa gene in which the coding sequence of the photoactivatable mEOS2 was inserted to determine the number and distribution of PfEMP1 on single knobs. The data were verified by quantitative fluorescence-activated cell sorting analysis and immuno-electron microscopy together with stereology methods. We show that knobs contain 3.3 ± 1.7 and 4.3 ± 2.5 PfEMP1 molecules, predominantly placed on the knob tip, in parasitized erythrocytes containing wild type and sickle haemoglobin, respectively. The ramifications of our findings for cytoadhesion and immune evasion are discussed.